Regulation of SREBPs by Sphingomyelin in Adipocytes via a Caveolin and Ras-ERK-MAPK-CREB Signaling Pathway. - Nehman Makdissy; Katia Haddad; Charbel Mouawad; Iuliana Popa; Mohamed Younsi; Philippe Valet; Laurent Brunaud; Olivier Ziegler; Didier Quilliot (PLoS ONE, 2015)
Sterol response element binding protein (SREBP) is a key transcription factor in insulin and glucose metabolism. We previously demonstrated that elevated levels of membrane sphingomyelin (SM) were related to peroxisome proliferator-activated receptor-γ (PPARγ), which is a known target gene of SREBP-1 in adipocytes. However, the role of SM in SREBP expression in adipocytes remains unknown. In human abdominal adipose tissue from obese women with various concentrations of fasting plasma insulin, SREBP-1 proteins decreased in parallel with increases in membrane SM levels. An inverse correlation was found between the membrane SM content and the levels of SREBP-1c/ERK/Ras/PPARγ/CREB proteins. For the first time, we demonstrate the effects of SM and its signaling pathway in 3T3-F442A adipocytes. These cells were enriched or unenriched with SM in a range of concentrations similar to those observed in obese subjects by adding exogenous natural SMs (having different acyl chain lengths) or by inhibiting neutral sphingomyelinase. SM accumulated in caveolae of the plasma membrane within 24 h and then in the intracellular space. SM enrichment decreased SREBP-1 through the inhibition of extracellular signal-regulated protein kinase (ERK) but not JNK or p38 mitogen-activated protein kinase (MAPK). Ras/Raf-1/MEK1/2 and KSR proteins, which are upstream mediators of ERK, were down-regulated, whereas SREBP-2/caveolin and cholesterol were up-regulated. In SM-unmodulated adipocytes treated with DL-1-Phenyl-2-Palmitoylamino-3-morpholino-1-propanol (PPMP), where the ceramide level increased, the expression levels of SREBPs and ERK were modulated in an opposite direction relative to the SM-enriched cells. SM inhibited the insulin-induced expression of SREBP-1. Rosiglitazone, which is an anti-diabetic agent and potent activator of PPARγ, reversed the effects of SM on SREBP-1, PPARγ and CREB. Taken together, these findings provide novel insights indicating that excess membrane SM might be critical for regulating SREBPs in adipocytes via a MAPK-dependent pathway.